Mentoring Children to Memorize Asmaul Husna Using Singing Method at The TPA Al-Muhajirin - Salsabila Asyifana DLT; Muslimah; Nurul Wahdah (International Journal of Community Engagement Payungi, 2022)
Mentoring children at Al-Muhajirin Sidomulyo TPA RT 03 in memorizing Asmaul Husna using the singing method is one of the work programs carried out by students of the Thematic Real Work Lecture (KKN) IAIN Palangka Raya. This assistance is a form of community service for Thematic KKN students. The method used in this service is the ABCD (Asset Based Community Development) method. This method has a main focus, namely broadcasting Islamic teachings by developing children's assets through memorizing Asmaul Husna. This mentoring activity aims to increase the potential of children in TPA in Islamic education, especially in the field of memorization. In the mentoring process, four stages are carried out, namely: 1) planning, 2) implementation, 3) observation, 4) reflection. Based on the results of the mentoring carried out, researchers saw that by using the singing method in memorizing Asmaul Husna, there was an increase in memorizing Asmaul Husna in children at Al-Muhajirin TPA. It is proven from the existence of 9 children who have not memorized Asmaul Husna, they have memorized 10 Asmaul Husna; from 5 children who memorized 12 Asmaul Husna, to memorize 20 Asmaul Husna with the correct recitation. Likewise with the quality of memorization, of the 15 children who lacked recitation, they became good and correct in recitation. Thus, mentoring children to memorize Asmaul Husna using the singing method at the Al-Muhajirin Sidomulyo TPA has an effect and has increased.